A Joint Multi-Layer Planning Algorithm for IP Over Flexible Optical Networks - Gkamas, Vasileios; Christodoulopoulos, Konstantinos; Varvarigos, Emmanouel (Journal of lightwave technology, 2015)
We consider the multi-layer network planning problem for IP over flexible optical networks, which consists of three subproblems at two layers: the Routing problem at the IP-layer (IPR), the routing, modulation level (RML), and the spectrum allocation (SA) problems at the optical layer. The input includes the IP end-to-end traffic matrix, the modular model of the IP/MPLS routers, and the feasible transmission configurations of the flexible optical transponders. Demands are served for their requested rates by selecting the IP/MPLS routers modules to be used, the routes in the IP (virtual) topology, and the corresponding paths and spectrum slots in the underlying optical topology, together with the optical transponders' configurations. The proposed algorithm follows a multi-cost approach that solves jointly the IPR, the RML, and the SA problems. It serves demands one-by-one, reusing existing equipment and favoring the deployment of new equipment that could also be reused by subsequent connections, aiming to minimize the total network cost. The problem definition is generic and the proposed algorithm is applicable to both fixed- and flex-grid optical networks. We evaluate the performance gains that can be obtained by the proposed joint multi-layer network planning solution, as opposed to a sequential planning solution that separately plans the IP and optical layers. We also compare a flexible network, using flex-grid optical switches and flexible optical transponders, to a mixed line rate (MLR) network, using fixed-grid or flex-grid optical switches but fixed optical transponders.